2008
DOI: 10.1111/j.1475-3995.2009.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of operational efficiencies in the Indian pharmaceutical industry

Abstract: Operational efficiencies of a firm play a crucial role in determining the survival and growth of a firm, especially when the industry is going through a dynamic structural transformation owing to external changes. In this paper, we explore the effect of managerial and strategic parameters on the degree of operational efficiency achieved by a firm in the Indian pharmaceutical industry using data envelopment analysis (DEA). During the period 1992-2002, the relaxation of import restrictions and foreign direct inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…Furthermore, in an important development, McDonald (2009) provides statistical foundation that the use of DEA and OLS is a consistent estimator, and if White's (1980) heteroskedastic consistent standard errors are calculated, large sample tests can be performed which are robust to heteroskedasticity and the distribution of the disturbances. Thus, following among others Saranga andPhani (2009), Chang et al (2008), and Banker and Natarajan (2005), the second stage regressions in this study are estimated by using the OLS method, while the standard errors are calculated by using White's (1980) cross-section tests to adjust for cross-section heteroskedasticity.…”
Section: Panel Regression Analysismentioning
confidence: 99%
“…Furthermore, in an important development, McDonald (2009) provides statistical foundation that the use of DEA and OLS is a consistent estimator, and if White's (1980) heteroskedastic consistent standard errors are calculated, large sample tests can be performed which are robust to heteroskedasticity and the distribution of the disturbances. Thus, following among others Saranga andPhani (2009), Chang et al (2008), and Banker and Natarajan (2005), the second stage regressions in this study are estimated by using the OLS method, while the standard errors are calculated by using White's (1980) cross-section tests to adjust for cross-section heteroskedasticity.…”
Section: Panel Regression Analysismentioning
confidence: 99%
“…All other DMUs are evaluated against this efficient frontier [11,12], first brought the idea of DEA in the context of engineering field. DEA has been extensively employed for performance evaluation in the different sectors like Banking [8], Airlines [21], Sports [40], education [31], pharmaceutical [41], Transport [2] and so on. One of the basic assumptions in the BCC-DEA model is non-negativity of input and output data.…”
Section: Variable Return To Scale-semi-oriented Radial Measure (Vrs-smentioning
confidence: 99%
“…Performance evaluation of the pharmaceutical sector using the non-parametric DEA approach has been carried out in India and output efficiency of firms has been studied by Majumder [9], Saranga, and Phani [28] and Mazumdar and Rajeev [27]. Keramidou et al [29] revealed inefficiencies arising from mismanagement and excess usage of capital in the when studying the Greek meat products industry.…”
Section: Some Of the Countries That Have Been Included In The Researcmentioning
confidence: 99%